Revealing the genotype-phenotype correlations of congenital hypothyroidism in Yunnan Province, Southwest China - Zhang, Yinhong; Wang, Shiyu; Li, Aoyu; Zhao, Wenjing; Xia, Fengyu; Chan, Ying; Lin, Junyue; Zhou, Xiaoyan; Li, Suyun; Feng, Na; Zhu, Baosheng; Li, Li (Frontiers in Endocrinology, 2025)
ContextCongenital hypothyroidism (CH) is a congenital endocrine disorder with diverse clinical presentations. The genotype–phenotype relationship has recently become a focal point in genetic etiology research on CH.ObjectiveTo explore the correlation between genetic variants and the clinical and biochemical characteristics of patients with CH in Yunnan Province, Southwest China.MethodsA retrospective analysis of 117 Yunnan-origin CH patients was conducted. Target regions capture next-generation sequencing (NGS) was used to screen for variations in all exons and their exon–intron boundaries in 27 CH-related genes. Patients were categorized into groups based on genetic variations; clinical outcomes were assessed through standardized follow-up.ResultsAmong the 117 CH patients, 91 carried gene variations related to CH, yielding a detection rate of 77.8%. Notably, variations in DUOX2, DUOXA2, and TG was most prevalent. Specifically, DUOX2 gene variations were found in 67 CH patients; these mutations encompassed 47 variant types, with K530X, R885L, and R1110Q being the most common in the Chinese cohort. CH patients exhibiting goiter and thyroid dysgenesis required a higher initial levothyroxine (L-T4) dose. As the number of gene variants increased, thyroid morphology gradually shifted toward “goiter” and “dysgenesis”. No significant differences were observed in biochemical characteristics or clinical outcomes among genetic variant groups.ConclusionsThis study provides valuable insights into the genetic landscape of CH in Yunnan Province, highlighting the importance of genes associated with thyroid dyshormonogenesis. Genotype cannot effectively be used to predict CH phenotype and prognosis. Standardized treatment and follow-up are crucial for positive outcomes in CH children.